Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1248/yakushi.131.1699
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Physiological Significance of Luminal Glutamate-sensing in the Gastrointestinal Functions

Abstract: Recent evidence indicates that free amino acids are nutrients as well as acting as chemical transmitters within the gastrointestinal tract. Gut glutamate research is the most advanced among 20 amino acids. Free glutamate carries the umami taste sensation on the tongue and a visceral sensation in the gut, especially the stomach. In theˆeld of taste physiology, the physiological meaning of the glutamate-derived chemical sense, the umami taste, has been proposed to be a marker of protein intake. Experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
12
0
2
Order By: Relevance
“…The present MRI observations suggest that the effects of glutamate are comparable to those of several GI hormones and neurotransmitters related with the brain-gut interaction (Willie et al 2001;Tsurugizawa et al 2009;Janssen et al 2011a,b;Karnani and Burdakov 2011;Nakayama 2011). As orexin and ghrelin affect both cephalic and gastric functions, L-glutamate contained in food acts as umami taste to evoke appetite through glutamate receptors in the oral cavity, and also promotes antroduodenal transport by organizing gastric and duodenal contractions presumably by facilitating vagal activity (Niijima 1991;Niijima and Meguid 1995;Uneyama 2011). In the small intestine, absorbed nutrients suppress the secretion of these hormones which promote feeding (Janssen et al 2011b).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The present MRI observations suggest that the effects of glutamate are comparable to those of several GI hormones and neurotransmitters related with the brain-gut interaction (Willie et al 2001;Tsurugizawa et al 2009;Janssen et al 2011a,b;Karnani and Burdakov 2011;Nakayama 2011). As orexin and ghrelin affect both cephalic and gastric functions, L-glutamate contained in food acts as umami taste to evoke appetite through glutamate receptors in the oral cavity, and also promotes antroduodenal transport by organizing gastric and duodenal contractions presumably by facilitating vagal activity (Niijima 1991;Niijima and Meguid 1995;Uneyama 2011). In the small intestine, absorbed nutrients suppress the secretion of these hormones which promote feeding (Janssen et al 2011b).…”
Section: Discussionsupporting
confidence: 51%
“…,b; Karnani and Burdakov ; Nakayama ). As orexin and ghrelin affect both cephalic and gastric functions, l ‐glutamate contained in food acts as umami taste to evoke appetite through glutamate receptors in the oral cavity, and also promotes antroduodenal transport by organizing gastric and duodenal contractions presumably by facilitating vagal activity (Niijima ; Niijima and Meguid ; Uneyama ). In the small intestine, absorbed nutrients suppress the secretion of these hormones which promote feeding (Janssen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health issues, like functional dyspepsia, irritable bowel syndrome and obesity are often related to eating habits. Because of that, the nutritional information from the gastrointestinal tract which affects the regulation of food digestion and nutrient absorption gains more importance as it also has an effect on eating behavior [81]. Other studies also showed that free glutamate in a high protein diet has a positive effect on delayed gastric emptying and abdominal unpleasantness after eating.…”
Section: Recent Results On Umami and Umami Compoundsmentioning
confidence: 99%